Un método para determinar observaciones influyentes en la SCE al ajustar modelos de diseños factoriales (2011)
This paper presents the generalization of the Qi statistics and the criterion to identify inﬂuential observations for the SCE when a linear model Y = Xβ +e of incomplete rank is ﬁtted using factorial design. Throughout the residual analysis, the later statistics is generalised under the classic assumption ei ∼ N(0;σ2) y Cov(ei,ej) = 0 si i 6= j).